Do Exchange Rate and Inflation Matters to Nigerian Economy? New Evidence from Vector Autoregressive (VAR) Approach - Usman, Mohammed A. M. (BOHR International Journal of Advances in Management Research, 2023)
Currency fluctuations and inflation are the natural norm for most major economies. Numerous factors influence economic growth, including a country’s exchange rate system performance, the outlook for inflation, and interest rate differentials. These are the most significant factors that hinder the economic growth of every nation. As a result, this analysis investigates the impact of exchange rate and inflation on Nigeria’s growth performance from 1986 to 2021. Impulse response and variance decomposition were estimated. The real gross domestic product (RGDP) was used as a proxy for growth performance, while the inflation rate (IFNR), real exchange rate (REXR), and interest rate (INTR) were also used as proxies. The results of impulse response and variance decomposition estimates in the short-run (third quarter) and long-run (tenth quarter) show that real exchange rate D(REXR), INTR, and IFNR all have a positive impact on RGDP variation, with values of 13.38%, 31.88%, and 22.40%, respectively, in the third quarter. In the long run (the 10th quarter), REXR contributed approximately 28.76% of the variation in RGDP. The interest rate contributed 24.14%, while the IFNR has contributed about 28.27% of the variation in RGDP in the long run. Therefore, summing the contributions of REXR, INTR, and INFR to RGDP, these variables contributed about 81.17% of the variation in RGDP in the long run. Hence, the research concluded that REXR, INTR, and IFNR have a positive effect on growth performance as proxied by RGDP in Nigeria within the period of the research. The research recommended that the government should provide a policy that will reduce the excess growth of aggregate demand (AD) in the economy, which will reduce inflationary pressure, in order to achieve the sustainable development goals (SDGs) of 2030 in Nigeria, which include restoring economic growth and macroeconomic stability through macroeconomic variables such as the exchange rate, inflation, and other significant variables.